Fatty acids profile of muffins available in the Portuguese market - Albuquerque, T.G. (2023)
Muffins are baked goods usually manufactured with flour, sugar and eggs, among other ingredients like fat, leavening agents and/or flavours. These are sweet bakery products highly appreciated due to their organoleptic features, but also for their convenience. However, besides some industry efforts to increase their nutritional quality, they are still perceived as a source of fat and sugar. AIM: Evaluation of the fatty acids profile of muffins from bakery stores and supermarkets, to deepen knowledge of the current situation of the Portuguese market and to identify future needs. Between June and August 2022, several types of muffins from the major supermarkets and bakery stores available in Lisbon were collected. In total, 8 composite samples of muffins were analysed. Fatty acids profile was determined by a transesterification method with a cold methanol solution of potassium hydroxide followed by gas chromatography analysis coupled to flame ionization detection. Polyunsaturated fatty acids were the major ones for 50% of the analysed samples. Saturated fatty acids content varied between 9.5 and 67% of total fatty acids. Only 1 sample had monounsaturated fatty acids as the most abundant (63%). There were no considerable differences found with respect to the fatty acids profile among the muffins of bakery stores and supermarket chains. Our findings suggest that there are still muffins available with high amounts of saturated fat, whose high intake can be a concern for public health. Moreover, the fact that muffins have a nutrition declaration (prepacked foods from supermarkets) does not mean that these are healthier than the ones from bakery stores (without nutrition declaration). Therefore, it is important to continue to investigate these products, to contribute with scientific evidence that can be further used to enhance their nutritional quality, for example by replacing the fat source.